Spatial and temporal variation in chlorophyll a concentration in the Eastern China Seas based on a locally modified satellite dataset. (1st May 2019) - Hao, Qiang; Chai, Fei; Xiu, Peng; Bai, Yan; Chen, Jianfang; Liu, Chenggang; Le, Fengfeng; Zhou, Feng
Abstract: Satellite chlorophyll a (Chl) is an essential parameter for large-scale studies on changes in the marine ecosystem and biogeochemistry. However, in the eastern China seas (ECSs), the coexistence and interaction of turbid and clear water pose challenges to the application of standard satellite Chl products to studies on phytoplankton dynamics. Based on the empirical modification of the OC-CCI (Ocean Colour Climate Change Initiative) standard products, we herein provide a locally modified chlorophyll a (LMC) dataset and compare the large-scale Chl distributions with satellite and in-situ Chl datasets. Compared with standard Chl, LMC has a higher correlation with in-situ data (R 2  = 0.58) and lower Bias (0.08) and is more consistent with the ship-measured Chl distributions. Using the LMC dataset, we analyzed the climatological Chl distributions in the ECSs and classified the Chl annual cycles into four types. Our results suggest that high Chl patterns not only rely on nutrient supply, but also relate to light conditions controlled by vertical mixing and suspended matter. The different Chl annual cycles are mainly caused by differences in the duration and range of nutrients and light limitation, and thus their distributions tend to vary with water depth. We believe that this work presents a more accurate dataset in the ECSs and can improve the understanding of local biogeochemical cycles. Highlights: We provided a new locally modified Chl dataset to reduce the overestimation of standard Chl products in ECSs. Large-scale Chl distributions from satellite and ship-measured observations were compared in the study area. Chl annual cycles in the ECSs were classified into 4 types and the environmental control mechanisms were revealed.